A genomic view of mosaicism and human disease - Biesecker, Leslie G.; Spinner, Nancy B. (Nature reviews. Genetics, 2013)
Key Points Mosaicism refers to the presence of genetically distinct cells within an organism that result from postzygotic mutational events. There are several different types of mosaicism at the organismal level that are categorized by the tissue distribution of the variant cells, including germline mosaicism and somatic mosaicism. Many different molecular types of genetic lesions — from single-nucleotide changes to large-scale chromosomal alterations — can be present in a mosaic form. Mosaicism can be generated not only by mutations resulting in variant genotypes but also by the reversion or rescue of abnormal genotypes. Mosaicism can lead to a diverse range of phenotypes, from overt to occult. It can also allow the clinical expression of mutations that would otherwise be lethal in the non-mosaic state, thus providing a broader assessment of genotype–phenotype correlations than do germline-inherited disorders. Modern genomic technologies have allowed the considerable frequency of mosaicism in humans to be increasingly recognized. For example, the frequency of chromosome aberrations in the early embryo has now been estimated as close to 70%. The complexity of the genetic causes and phenotypic consequences of mosaicism pose challenging dilemmas for the diagnosis, prognosis and mechanistic understanding of mosaic diseases in affected individuals. Mosaicism refers to genetic heterogeneity within an organism that arises from postzygotic mutational events. This Review describes our latest understanding of the diverse types and widespread nature of mosaicism that underlies normal human variation and, in particular, a wide range of clinical diseases. Genomic technologies, including next-generation sequencing (NGS) and single-nucleotide polymorphism (SNP) microarrays, have provided unprecedented opportunities to assess genomic variation among, and increasingly within, individuals. It has long been known that cancer is a mosaic genetic disorder, but mosaicism is now apparent in a diverse range of other clinical disorders, as indicated by their tissue distributions and inheritance patterns. Recent technical advances have uncovered the causative mosaic variant underlying many of these conditions and have provided insight into the pervasiveness of mosaicism in normal individuals. Here, we discuss the clinical and molecular classes of mosaicism, their detection and the biological insights gained from these studies.